2008
DOI: 10.1292/jvms.70.99
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics of Tylosin or Florfenicol after a Single Intramuscular Administration at Two Different Doses of Tylosin-Florfenicol Combination in Pigs

Abstract: ABSTRACT. Clinical pharmacokinetic profiles were investigated following intramuscular (i.m.) administration to pigs with a commercial tylosin-florfenicol combination product at a dose of 2.5 mg/kg tylosin and 5 mg/kg florfenicol or 10 mg/kg tylosin and 20 mg/kg florfenicol. The quantitation limit (QL) of florfenicol was 0.1 µg/ml, the inter-day and intra-day precision (CV%) were both beow 10%. The quantitation limit (QL) of tylosin was 0.05 µg/mL. The pharmacokinetic characteristics after i.m. doses were fitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…This is longer than the values previously reported for other animal species (calf 2.24 h, buffalo 2.40 h, camel 2.73–3.71 h, pig 3.01–3.88 h, sheep 2.3–6 h, and goat 5 h) [15, 21, 24, 25]. The variability of the elimination half-lives of this antibiotic in different animal species is attributed to the anatomical and physiological differences between these species as well as to the differences in the formulation of the drug [25].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This is longer than the values previously reported for other animal species (calf 2.24 h, buffalo 2.40 h, camel 2.73–3.71 h, pig 3.01–3.88 h, sheep 2.3–6 h, and goat 5 h) [15, 21, 24, 25]. The variability of the elimination half-lives of this antibiotic in different animal species is attributed to the anatomical and physiological differences between these species as well as to the differences in the formulation of the drug [25].…”
Section: Discussionmentioning
confidence: 67%
“…It was ascertained that, following the IM administration of tylosin and the SC administration of tilmicosin, the serum concentration-time curves of both antibiotics were consistent with the two-compartment open model (Figures 1 and 2). Similarly, while the two-compartment open model has been used for calculations in previous research [1621], it has been observed that, in studies in which a consistency analysis (based on direct observation and AIC) was not performed [8, 2224], the noncompartmental model was used.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the intramuscular (IM) pharmacokinetics of the combination in pigs [13]. In the present study, we evaluated the disposition kinetics of florfenicol and tylosin after intravenous (IV) and IM injection of the combination product to dogs.…”
mentioning
confidence: 99%
“…It is worth noting that the number of applications was half that used by Marsteller et al (2001), which demonstrates clear practical advantage based on the time spent with handling animal medication. With respect to the active principle used for the treatment of PPE in the present study, tylosin is a macrolide, bacteriostatic agent that can act as a bactericide when in high concentrations (Kim et al 2008). Macrolides bind to the subunit (50s) of the bacterial ribosome by inhibiting bacterial protein synthesis (Barcellos et al 2012).…”
Section: Table 2 Comparison Between Mean Weight Of Animals In the Comentioning
confidence: 98%
“…Among them, tylosin, chlortetracycline, and tiamulin are the most frequently used (Burch 2000). Tylosin is a macrolide antibiotic that inhibits bacterial protein synthesis (Kim et al 2008), acting as a bacteriostatic agent, and may also act as a bactericide when used in high concentrations (Barcellos et al 2012). McOrist et al (1997) demonstrated that in-feed tylosin phosphate is effective in the prevention and treatment of PPE.…”
Section: Introductionmentioning
confidence: 99%